Occlusal management for a patient with aural symptoms of unknown etiology: a case report - Torii, Kengo (BioMed Central, 2007)
BACKGROUND: Although the discrepancy between the habitual occlusal position (HOP) and the flat bite plate-induced occlusal position (BPOP) (regarded as the muscular physiological reference position) has been recently reported to be related to symptoms of temporomandibular disorders (TMDs), it still remains unclear whether the occlusal equilibration in the reference position is effective to resolve TMD-related discrepancy and symptoms. Aural symptoms (otalgia, tinnitus, vertigo et cetera) have been included under TMD symptoms. METHODS: To examine the effect of occlusal equilibration for the treatment of TMDs, occlusal equilibration was performed for a patient with aural symptoms (otalgia, tinnitus and vertigo) of unknown etiology in the right ear. An occlusal analysis was performed on this patient with dental models mounted on an articulator after relieving painful symptoms by an appliance therapy and a discrepancy was identified (p < 0.005). Occlusal equilibration in the BPOP was then performed for the patient by selective tooth grinding, because it was estimated that the interocclusal space between upper and lower occlusal surfaces would be rectified by selective grinding. RESULTS: At completion of treatment, the discrepancy was not significant (p > 0.25), and the patient's right condyle had shifted 2.8 mm posteromedially in the horizontal plane, and the left condyle had shifted 1.0 mm laterally in the voluntarily closed position from the previous HOP. The aural symptoms of the patient were resolved, and there has been no recurrence to date after a two-year follow-up period. CONCLUSION: An occlusal analysis should be performed in patients exhibiting TMD symptoms to identify the presence or absence of any discrepancy between the HOP and the BPOP. If a discrepancy exists, occlusal equilibration should be attempted in the reference position.